Analisis Laporan Realisasi Anggaran Dalam Menilai Kinerja Keuangan Pada DP3AKB Kabupaten Jember Tahun 2024 - Silvi Tri Handayani; Lidia Ainun Fadilla; Salman Farizi (Menulis: Jurnal Penelitian Nusantara, 2025)
The budget realization report is a financial statement issued by the government or an agency before preparing the cash flow statement and balance sheet. The Women's Empowerment, Child Protection, and Family Planning Service, as part of the government, is obligated to compile this report annually as a form of accountability to the public for the allocated funds. This study utilizes the 2024 budget realization report and analyzes it from three perspectives: variance, economic level, and effectiveness. The analysis aims to assess the financial performance of the Women's Empowerment, Child Protection, and Family Planning Service, ensuring efficiency and the absence of wasteful spending. The research employs a quantitative descriptive method, where the collected data is structured and analyzed to illustrate the findings.